2022
DOI: 10.1002/jper.21-0598
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor regulates specific innate immune sensor responses in gingival epithelial cells

Abstract: Background:The gingival epithelium protects periodontal tissues and the alveolar bone by maintaining a steady state of regulated inflammatory surveillance, also known as healthy homeostasis. Accordingly, the repertoire of receptors present within the gingival epithelium showcases its ability to recognize microbial colonization and contribute to bacterial sensing. Macrophage migration inhibitory factor (MIF) is one of many cytokines that are expressed in this protective state and is involved in neutrophil regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…The PT Mif-/-and PGPD Mif−/− groups did not develop clinical signs and preserved tissue continuity compared to the PT WT and PGPD WT groups. These observations were corroborated by a histometric analysis 44,45 and supported that the presence of MIF influences the exacerbation of PT during pregnancy. In particular, the loss of tissue from the PGPD WT and PT WT groups was similar, with no significant differences, although both showed tissue destruction, mainly on the palatal side, with a 31% greater loss than on the buccal side.…”
Section: Discussionsupporting
confidence: 64%
“…The PT Mif-/-and PGPD Mif−/− groups did not develop clinical signs and preserved tissue continuity compared to the PT WT and PGPD WT groups. These observations were corroborated by a histometric analysis 44,45 and supported that the presence of MIF influences the exacerbation of PT during pregnancy. In particular, the loss of tissue from the PGPD WT and PT WT groups was similar, with no significant differences, although both showed tissue destruction, mainly on the palatal side, with a 31% greater loss than on the buccal side.…”
Section: Discussionsupporting
confidence: 64%
“… 18 The decreased survival rate of HGEs will destroy the homeostasis of oral microorganisms, leading to the accumulation of oral pathogenic microorganisms, the formation of dental plaque and the development of periodontitis. 38 From our results, a high concentration of CS and e-cigarettes both reduced cell survival. Thus, CS had a greater impact on cell survival which suggested that tobacco might be more likely to cause periodontitis than e-cigarettes.…”
Section: Discussionmentioning
confidence: 56%
“…HGEs play an important role in oral gingival tissue, being the first cells to be exposed to the environment, acting as a barrier against invading bacteria and acting as an antibacterial agent . The decreased survival rate of HGEs will destroy the homeostasis of oral microorganisms, leading to the accumulation of oral pathogenic microorganisms, the formation of dental plaque and the development of periodontitis . From our results, a high concentration of CS and e-cigarettes both reduced cell survival.…”
Section: Discussionmentioning
confidence: 62%